2017
DOI: 10.1371/journal.pone.0189060
|View full text |Cite
|
Sign up to set email alerts
|

The acute glucose lowering effect of specific GPR120 activation in mice is mainly driven by glucagon-like peptide 1

Abstract: The mechanism behind the glucose lowering effect occurring after specific activation of GPR120 is not completely understood. In this study, a potent and selective GPR120 agonist was developed and its pharmacological properties were compared with the previously described GPR120 agonist Metabolex-36. Effects of both compounds on signaling pathways and GLP-1 secretion were investigated in vitro. The acute glucose lowering effect was studied in lean wild-type and GPR120 null mice following oral or intravenous gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 49 publications
7
32
0
Order By: Relevance
“…The specific configuration of cilia in the context of islet cells is therefore of interest, and future studies could address how localized cAMP signals are propagated to the secretory structures in islet cells. In addition to signaling mechanisms revealed here, prior reports 36 suggest that FFAR4 stimulation may lead to activation of phospholipase C (PLC) and subsequent elevation of intracellular Ca 2 ; we have found that exposure of MIN6 and α-TC9 cells to PLC inhibitor U73122 also attenuates FFAR4-stimulated insulin and glucagon secretion (data not shown). Thus, additional studies will also be useful for understanding how the same ciliary GPCR can simultaneously and locally modulate multiple signaling pathways, and whether this multiplex signaling is achieved by dynamic control of localized intra-or juxta-ciliary signaling.…”
Section: Discussionsupporting
confidence: 56%
“…The specific configuration of cilia in the context of islet cells is therefore of interest, and future studies could address how localized cAMP signals are propagated to the secretory structures in islet cells. In addition to signaling mechanisms revealed here, prior reports 36 suggest that FFAR4 stimulation may lead to activation of phospholipase C (PLC) and subsequent elevation of intracellular Ca 2 ; we have found that exposure of MIN6 and α-TC9 cells to PLC inhibitor U73122 also attenuates FFAR4-stimulated insulin and glucagon secretion (data not shown). Thus, additional studies will also be useful for understanding how the same ciliary GPCR can simultaneously and locally modulate multiple signaling pathways, and whether this multiplex signaling is achieved by dynamic control of localized intra-or juxta-ciliary signaling.…”
Section: Discussionsupporting
confidence: 56%
“…Given that pro-inflammatory cytokines and chemokines, like tumor necrosis factor alfa (TNF-α), interleukin-6 (IL-6) and resistin, overproduced by the dysfunctional adipose tissue in obesity, can activate intracellular pathways that trigger IR in insulin-target tissues [15], the anti-inflammatory potential of PUFAs may indirectly improve the peripheral insulin responsiveness, reducing the risk of glyco-metabolic alterations in patients with IR [49]. Additionally, PUFAs can bind and stimulate G-protein-coupled receptors (GPCRs) which play important roles in regulating glucose metabolism, such as GPR120, thereby leading to increased secretion of the glucagon-like peptide 1 (GLP-1) hormone from enteroendocrine L-cells [50]. By stimulating insulin release from pancreatic β-cells, with immediate consequences of increased glucose uptake from skeletal muscles, raised GLP-1 levels may in turn limit postprandial hyperglycemia [51].…”
mentioning
confidence: 99%
“…This receptor is involved in diverse processes, including insulin sensitization and glucose uptake. Low levels of FFAR4 expression or function have been correlated with increased plasma glucose levels [14,18] and high HOMA-IR [13,18,19].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Blocking the glucagonlike peptide-1 receptor with antagonists results in the inhibition of hypoglycemic effects induced by FFAR4 activation. Therefore, dysfunction of FFAR4 could impact insulin release, leading to an increase in HOMA-IR [18]. A recent study has shown an association between 4 SNPs of the FFAR4 gene (rs11187537, rs17108973, rs7081686, and rs17484310) and fasting insulin levels and HOMA-IR.…”
Section: Discussion/conclusionmentioning
confidence: 99%